Study Of Gan Low Dimensional Structures On Silicon Substrates Grown By Thermal Vapor Deposition For Photodiode And Solar Cell Applications - Abdelrahman, Kamaleldin Mohamed Abdalla (2014)
Gallium nitride (GaN) is a greatly promising wide band gap semiconductor with applications in high power electronic and optoelectronic devices. Heterostructure solar cell involving GaN low Dimensional (low D) structures on single crystalline silicon (Si) substrates are the preferable choice as they have excellent internal quantum efficiencies, large open-circuit voltages, and low processing cost. This thesis examines the growth of GaN low D structures on Si substrates using inexpensive thermal vapor deposition (TVD) techniques for solar cell and photodiode (PD) devices. The growth was achieved using two methods. The first method involved the growth of GaN low D structures on n-Si (111) in NH3-free environments by TVD via thermal evaporation of GaN powder under different carrier gases, substrate temperatures and deposition times. The result showed that the morphology and shape of GaN low D structures are highly dependent on each parameter. The X-ray diffraction and Raman spectra of the low D structures indicated that the GaN structure had a hexagonal wurtzite structure. The TVD is optimized by using 1h deposition time and 1000ᵒC temperature to obtain uniform dense low D structures with good crystalline quality and hence enhanced performance of PD and solar cell devices.